If I Were the Boss of You...This Is How All Meetings Would Be Run - Coleman, Tara (My University, 2021)
Some meetings are invigorating, some a struggle, and some make participants feel like they are riding on the hot mess express. Attendees may be unsure of why they are in the meeting. The usual person dominates the conversation without adding anything of substance. Meeting members might leave with a completely different understanding of what happened than someone else. This session provides tangible tips for shaping meeting expectations and roles, introduces free or low-cost tools that allow for voices to be heard that would otherwise be silent (or talked over), and supplies ways to wisely use and respect everyone’s time.
Keywords: Meetings; Meeting facilitation; Meeting tools; Expectations and roles; Brick & Click